“My Entire World Stopped”: College Students’ Psychosocial and Academic Frustrations during the COVID-19 Pandemic - Hagedorn, Rebecca L.; Wattick, Rachel A.; Olfert, Melissa D. (Applied Research in Quality of Life, 2022)
The COVID-19 pandemic disrupted normalcy for college attending young adults which resulted in a loss of the campus environment and classroom setting. This change in setting may interfere with a student’s personal and academic wellbeing. This study used an online survey to evaluate college students’ academic and psychosocial frustrations during the COVID-19 pandemic. Data were collected from March–April 2020 at a land-grant university in the Appalachian region. Data were available from 2643 undergraduate and graduate students. There was a 65.8% and 15.7% increase in the number of students who reported their learning and health as fair, poor, or very poor after the COVID-19 pandemic, respectively. Qualitative responses were coded and 8 themes and 24 subthemes emerged. College students expressed frustrations regarding technology, classwork, research, family, social, emotional, behavioral, and financial aspects of life. These results can be used by higher education administration, faculty, and staff when planning for online courses. Ensuring that student frustrations and barriers to success are recognized and considered may help prevent students departing from higher education during this time.